(NmODELIROWANIE WODOHOZQJSTWENNYH SISTEM ARIDNOJ ZONY sssr (B/s - (NwOROPAEW(B, (NgRIGORIJ wASILXEWI^s; (NiSMAJYLOW(B, (NgABIL hUDU[EWI^s; (NfEDOROW(B, (NwLADIMIR mIHAJLOWI^s; (NwENDROW(B, (Ns(B.(Nl(B.s; (NiNSTITUT WODNYH PROBLEM an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1984)
(NbIBLIOGR(B. 146 (NNAZ(B.s
Keywords: (NfIZI^ESKAQ GEOGRAFIQs